1992
DOI: 10.1093/carcin/13.7.1127
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization by 32P-postlabelling of DNA adducts induced by a Fenton-type oxygen radical-generating system

Abstract: Reactive oxygen species can give rise to numerous modifications of DNA. We have investigated the formation of such modifications using the nuclease P1 digestion method of the 32P-postlabelling procedure for the detection of DNA damage. Analysis of DNA that had been treated with a Fenton-type system of copper (or iron) ions and H2O2 resulted in the detection of up to ten discrete 32P-labelled spots, displaying chromatographic characteristics similar to aromatic adducts, on PEI-cellulose TLC. Maximum total level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
36
1
1

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 23 publications
4
36
1
1
Order By: Relevance
“…Our results using the 32 P postlabeling assay indicate that the "putative intrastrand purine dimers" (Carmichael et al, 1992, Lloyd et al, 1997 which were proposed as candidate neurodegenerative lesions in XP by (Satoh et al, 1993) are also dinucleotides containing cyclodA. However, because the postlabeling studies were done in different laboratories, and used different reagents and chromatographic solvents, it is not absolutely certain that the same adducts were being studied in both cases.…”
Section: Criterion 3: Cyclopurine-deoxynucleosides Are Endogenous Dnamentioning
confidence: 81%
See 1 more Smart Citation
“…Our results using the 32 P postlabeling assay indicate that the "putative intrastrand purine dimers" (Carmichael et al, 1992, Lloyd et al, 1997 which were proposed as candidate neurodegenerative lesions in XP by (Satoh et al, 1993) are also dinucleotides containing cyclodA. However, because the postlabeling studies were done in different laboratories, and used different reagents and chromatographic solvents, it is not absolutely certain that the same adducts were being studied in both cases.…”
Section: Criterion 3: Cyclopurine-deoxynucleosides Are Endogenous Dnamentioning
confidence: 81%
“…These authors used the in vitro NER assay (Wood et al, 1988) to show that exposure of DNA to oxygen radicals generated a class of DNA lesion(s) that are normally repaired by the NER, and proposed that oxidative stress could be the source of the DNA damage that causes neuronal death in XP patients. In considering the possible identities of oxidatively-induced lesions that are repaired by NER, Satoh et al suggested "putative intrastrand purine dimers" detected using the 32 P-postlabeling method (Carmichael et al, 1992; see also Randerath et al, 1991) as well as cyclopurine-deoxynucleosides. The possible role of cyclopurine-deoxynucleosides in XP neurological disease had also been considered by Robbins and colleagues (Dizdaroglu et al, 1987).…”
Section: Oxidative Stress As a Possible Source Of Neurodegenerative Dmentioning
confidence: 99%
“…A primary candidate for an alteration in DNA that could produce the double mutation is the crosslinking of two adjacent cytosines. There is evidence that exposure of dinucleotides to oxidative damage mediated by Cu/H202 results in a crosslink between the two bases, although cytosine crosslinks were not assayed (29). The finding that CC -> TT substitutions are observed after damage to DNA by both reactive oxygen species and UV-irradiation suggests that both types of agents may produce a similar intermediate, leading to a stable mutagenic adduct.…”
Section: T-t T-t T-t T-t T-t T-t T-t T-t T-t T-t T-t T-t T-t 5'-c-c-amentioning
confidence: 98%
“…19 Other type II I-compounds may represent base-base 1,20,21 or base-sugar intrastrand crosslinks. 21 Dinucleotides containing cA present as bulky ROSinduced DNA lesions.…”
mentioning
confidence: 99%